2017
DOI: 10.1371/journal.pone.0171559
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the abscopal effect in preclinical models: Is the biologically effective dose a relevant physical trigger?

Abstract: BackgroundPreclinical in vivo studies using small animals are considered crucial in translational cancer research and clinical implementation of novel treatments. This is of paramount relevance in radiobiology, especially for any technological developments permitted to deliver high doses in single or oligo-fractionated regimens, such as stereotactic ablative radiotherapy (SABR). In this context, clinical success in cancer treatment needs to be guaranteed, sparing normal tissue and preventing the potential spre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 55 publications
1
74
0
2
Order By: Relevance
“…On the basis of the preclinical studies (TABLE 1), the optimal dosing and fractionation strategy for each cancer type has not been determined yet, as both single and fractionated radiotherapy doses have been reported to boost abscopal responses when combined with different immunotherapies 23,34,41 . For example, a preclinical study combining radiotherapy with anti-CTLA4 for breast and colon cancer models concluded that 3 fractions of 8 Gy and 5 fractions of 6 Gy are superior to a single ablative dose of 20 Gy (REF.…”
Section: Boosting the Abscopal Effectmentioning
confidence: 99%
“…On the basis of the preclinical studies (TABLE 1), the optimal dosing and fractionation strategy for each cancer type has not been determined yet, as both single and fractionated radiotherapy doses have been reported to boost abscopal responses when combined with different immunotherapies 23,34,41 . For example, a preclinical study combining radiotherapy with anti-CTLA4 for breast and colon cancer models concluded that 3 fractions of 8 Gy and 5 fractions of 6 Gy are superior to a single ablative dose of 20 Gy (REF.…”
Section: Boosting the Abscopal Effectmentioning
confidence: 99%
“…A recent meta-analysis study shows when the BED increases, the occurrence rate of abscopal effects also increases due to immunological responses in preclinical models [17]. However, studies have not yet determined whether different regimens with the same BED (when the biological effects of the regimens are equal) have different immunogenic effects, whether they affect tumor recurrence associated with immunological responses, In addition, can these regimens respond differently to combination therapy?…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that IR with different dose per fraction schemes could change the tumor immune microenvironment (32,33) and create "in situ vaccine" to induce an effective abscopal effect on remote tumors (off target) (34,35). This study, using two HCC mouse models, demonstrated that hypofractionated IR was more effective to create the abscopal effect with a high dose per fraction in the same 40-Gy total dose, that is, ≥4 Gy/fraction.…”
Section: Discussionmentioning
confidence: 79%